Kidney transplantation and hyperparathyroidism - O. N. Vetchinnikova (Трансплантология (Москва), 2017)
Successful kidney transplantation eliminates endocrine and metabolic disorders that predispose to the development of hyperparathyroidism, the complication typical for the chronic kidney disease; but the process of recovery from mineral and bone disorders is slowed down. The highest incidence of post-transplant hyperparathyroidism is recorded in the first postoperative year. The risk factors for its development or persistence include the high blood levels of parathyroid hormone, calcium, phosphorus, and/or alkaline phosphatase, a prolonged dialysis therapy, severe hyperparathyroidism in the preoperative period, vitamin D deficiency, a suboptimal transplanted kidney function, and also the recipient's previous history of subtotal or incomplete parathyroidectomy. The characteristic clinical and laboratory signs of posttransplant hyperparathyroidism are bone lesions, kidney graft abnormalities, hypercalcemia, and hypophosphatemia. The diagnostic algorithm includes monitoring the markers of mineral and bone metabolism, determining the bone mineral density, and imaging of thyroid glands. Correction of post-transplant hyperparathyroidism is performed surgically or pharmacologically. The article specifies the indications to, the extent and timing of parathyroidectomy, discusses the use of native vitamin D formulations, its analogues, and calcimimetics.